Analisis Pengawasan Pembiayaan Syariah Pada Perbankan Syariah Sebagai Penerapan Prinsip Kehati-hatian (Studi Kasus Bank Syariah Indonesia KCP Serang Timur) - Arief, Muhammad; hoh, Sharifurrohman; Rujikartawi, Erdi; Septiani (TSARWAH, 2023)
Sharia banks have the main function of channeling public funds in the form of financing. Financing at sharia banks is an effort to make a profit. However, on the other hand, it also has high risks and can even result in banking losses. The quality of financing must be maintained because it is included in most of the productive assets of sharia banks. The aim of this research is to analyze the impact of supervision of sharia bank financing through the precautionary principle. This type of research includes field research and uses descriptive qualitative methods. Research was conducted at BSI KCP East Serang to obtain data sources from employees, managers or policy makers by means of observations, documentation and interviews regarding mechanisms and strategies in implementing sharia financing supervision. The research results obtained are that BSI KCP East Serang has implemented good corporate governance (GCG) which is inherent in BSI's business activities. The Bank implements it based on the principle of prudence and in accordance with the existing theory that analyzes financing using the 5C + 1S principles, and complies with all applicable regulations and legislation. The application of the principle of prudence in sharia financing at BSI KCP East Serang is carried out through two forms of supervision, namely preventive supervision and repressive supervision. The application of the principle of prudence to the supervision of financing provision has had a positive impact, namely improving the health of the bank.